Experimental Analysis on Uptake of Heavy Metals by Hyperaccumulating Plants Grown on Contaminated Soil and Wastewater - Monisha, S.; Sangeetha, S.P. (Journal of Environmental Accounting and Management, 2026)
The accumulation of heavy metals in soil and water adversely affects the environment, human health, and food quality. Contamination primarily arises from industrial effluents, classified into non-metallic and metallic pollutants. This study investigates the effects of arsenic and chromium on plant growth and their uptake by Medicago sativa and Brassica juncea.Developing effective and economical methods to remove these heavy metals is crucial. Medicago sativa and Brassica juncea were chosen for their potential to extract chromium and arsenic from soil and water. The experiment utilized arsenic and chromium concentrations of 2, 4, 6, 8, and 10 ppm, with a maximum of 1000 mg/L. Growth parameters, including plant height and seed germination, were monitored, soil pH analyzed, and arsenic and chromium accumulation assessed using ICP-MS after 45 days. Results show Brassica juncea accumulates more chromium in its roots (68 mg/kg at 10 ppm) than in shoots and leaves, while arsenic uptake was lower (51 mg/kg). Similarly, Medicago sativa exhibited higher chromium accumulation (38 mg/kg in roots at 10 ppm) compared to arsenic (28 mg/kg). Both plants effectively remove heavy metals, particularly chromium, from contaminated sites. This environmentally sustainable and cost-effective phytoremediation approach offers a natural solution for reducing soil contamination. The study concludes that Brassica juncea is more efficient for chromium uptake, while Medicago sativa excels in arsenic absorption across roots and aerial parts.